Niveles de contenido ruminal en ensilaje del pasto king grass morado (Pennisetum spp) y valoración bromatológica en cuatro tiempos de conservación - Franco Bonilla, Jorge Luis (2015)
The objective of the research was to assess levels of ruminal content in silage grass purple King Grass (Pennisetum) and valuation bromatological four storage times. Research conducted in the canton La Mana, La Playita experimental center located WGS 84: Latitude S0 ° 56 '27 "Longitude W 79 ° 13' 25", at a height of 220 meters. The investigation lasted 112 days of fieldwork. The treatments resulted from the application of different combinations of rumen contents levels (0%, 3%, 6%, 9% and 12%) at various storage times (28, 56, 84 and 112 days), this will employed Completely Random Design (DCA), consisting of 20 treatments and four repetitions. For the difference between treatment means multiple range test of Tukey (P ≤ 0.05) was used in the variables evaluated the potential of hydrogen (pH) lower at 28 and 56 days are given in the treatment (King Grass purple CR + 6%) 5.98 and 5.60; at 84 days in treatment (King Grass purple + CR 9%) with 8.31 and 112 days the treatments (King Grass purple + CR 0%) 6.01; the average temperature in the different times of opening 28 - 56 - 84 and 112 showed a uniform behavior, this falling below 35 ° C with an average (X = 30.5 ° C). The best result of dry matter is provided by treatments with 0%, 3%, 6%, 9% and 12% of rumen contents to 112 days with percentages of 40.37; 30; 66; 33.17; M.S. 29.59 and 48.14%, in that order. The best shelf for silage grass purple King Grass (Pennisetum spp) is given to the 28 days of storage at 12% of rumen contents, where a protein level of 9.10% is obtained.